2015
DOI: 10.1186/s12903-015-0045-3
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis associated with plasminogen deficiency: a case report

Abstract: BackgroundPlasminogen deficiency is a rare autosomal recessive disease, which is associated with aggressive periodontitis and gingival enlargement. Previously described treatments of plasminogen deficiency associated periodontitis have shown limited success. This is the first case report indicating a successful therapy approach consisting of a non-surgical supra- and subgingival debridement in combination with an adjunctive systemic antibiotic therapy and a strict supportive periodontal regimen over an observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The fact that only 32% of patients who suffer from PLG Type 1 deficiency develop ligneous periodontitis strongly supports the notion that external triggers, i.e., trauma or infection, may play an Case Reports in Dentistry additional significant role in the pathogenesis of this disease [5,10,31]. The average age of patients reported in the literature with ligneous periodontitis is 12-18 years, while isolated cases have been reported in older patients; these differences may reflect variability in PLG activity due to different plasminogen gene mutations [32]. Histopathological examination was done to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The fact that only 32% of patients who suffer from PLG Type 1 deficiency develop ligneous periodontitis strongly supports the notion that external triggers, i.e., trauma or infection, may play an Case Reports in Dentistry additional significant role in the pathogenesis of this disease [5,10,31]. The average age of patients reported in the literature with ligneous periodontitis is 12-18 years, while isolated cases have been reported in older patients; these differences may reflect variability in PLG activity due to different plasminogen gene mutations [32]. Histopathological examination was done to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 72%
“…Several therapeutic approaches to reduce the bacterial load to decrease the inflammation and thus the progression of the disease have been attempted; these procedures include scaling and root planing, chlorhexidine rinsing, administration of antibiotics, and periodontal surgery [9,25,30]. Neering et al have reported that patients with PLG-deficiency Type I may benefit from nonsurgical periodontal therapy including full mouth disinfection in combination with adjunctive antibiotic therapy and a strict supportive periodontal therapy regime every three months [32]. Most of the reports have been described as failures due to rapid gingival regrowth and progressive bone loss [5].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such patients present with deposition of fibrin at various mucosal sites leading to ocular disease (conjunctivitis), oral mucosal disease (ligneous periodontitis), lung, vaginal and gastrointestinal tract involvement [3][4][5]. In the oral mucosa, local deposition of fibrin is hypothesized to lead to severe soft tissue and bone destruction around teeth and often loss of the entire dentition in adolescence [6][7][8][9]. Mucosal inflammation in areas surrounding the dentition and destruction of underlying bone are also the hallmarks of the common human oral mucosal disease, periodontitis [10,11].…”
Section: Well-established Appreciation Of This General Concept Specimentioning
confidence: 99%
“…Although the PD risk allele of rs4252120 was found to be strongly associated with lipoprotein(a) level and CAD risk (Qi et al 2012), LPA does not seem to represent a so-far-undetected genetic risk factor shared between PD and CAD/MI. The fact that PLG deficiency-a rare autosomal recessive disease (1.6 in 1 million individuals) caused by mutations of PLG-is known to be associated with severe early-onset PD (Neering et al 2015) suggests that PLG may be directly and causally related to AgP rather than due to linkage disequilibrium with the CAD-associated LPA SNPs.…”
Section: Genetic Variants Shared Between Aggressive or Chronic Pd And Coronary Heart Diseasementioning
confidence: 99%